Gene Therapy for Neurodegenerative Disease: Clinical Potential and Directions - Zhu, Xiaolin; Zhang, Yu; Yang, Xin; Hao, Chunyan; Duan, Hubin (Frontiers in Molecular Neuroscience, 2021)
The pathogenesis of neurodegenerative diseases (NDD) is complex and diverse. Over the decades, our understanding of NDD has been limited to pathological features. However, recent advances in gene sequencing have facilitated elucidation of NDD at a deeper level. Gene editing techniques have uncovered new genetic links to phenotypes, promoted the development of novel treatment strategies and equipped researchers with further means to construct effective cell and animal models. The current review describes the history of evolution of gene editing tools, with the aim of improving overall understanding of this technology, and focuses on the four most common NDD disorders to demonstrate the potential future applications and research directions of gene editing.